Obstetric Care For Primigravida Mothers With Antepartum Depression Before Delivery At Pratama Siti Kholijah Clinic Jl. Marelan I, Terjun, Kec. Medan Marelan - Fauza, Rahmawani; Rambe, Nova Linda (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2023)
Antepartum depression or stress is a complication of pregnancy risks and negative experiences in a woman's life. According to a systematic review, the incidence of mental health disorders such as depression and anxiety disorders in mothers in developing countries was recorded to have an average of 15.6% during pregnancy and 19.8% after delivery. A study showed the prevalence of antepartum depression, amounting to 26.6%. Depression during pregnancy has been shown to produce unwanted perinatal eg preterm delivery, low birth weight, preeclampsia, low Apgar scores at 1 and 5 minutes. The adrenal cortex secretes cortisol in response to ACTH, diurnal rhythms, and stress. Guided imagery relaxation techniques using soothing words and sounds; directs the user to imagine a psychological or physiological state in a relaxed manner. Researchers provide comprehensive midwifery care for pregnant women, maternity, postpartum, BBL, neonates and family planning using a midwifery management approach to Mrs "I" with Antepartum Depression. Care in this study by observation, evaluation, counseling. The subject of this care is Mrs “I” with Antepartum Depression at Siti Kholijah Primary Clinic. Comprehensive midwifery care for Mrs. "I" during the third trimester of pregnancy with antepartum depression before delivery, in normal labor and spontaneous delivery, during the postpartum period with normal postpartum, BBL with BBLN, neonates with normal neonates, and being an acceptor for condom. This research activity is about the management of antepartum depression in primigravida women before delivery. Researchers conducted observations, evaluation, and counseling to mothers. Observations and evaluations were carried out by knowing and assessing emotional conditions, levels of fatigue, and support for mothers. The mother's hydration status also needs to be considered and if possible, the mother can be asked to eat even in small portions so that she can gather energy for delivery.